First-Time Migration in Juvenile Common Cuckoos Documented by Satellite Tracking. - Marta Lomas Vega; Mikkel Willemoes; Robert L Thomson; Jere Tolvanen; Jarkko Rutila; Peter Samaš; Roine Strandberg; Tomáš Grim; Frode Fossøy; Bård Gunnar Stokke; Kasper Thorup (PLoS ONE, 2016)
Being an obligate parasite, juvenile common cuckoos Cuculus canorus are thought to reach their African wintering grounds from Palearctic breeding grounds without guidance from experienced conspecifics but this has not been documented. We used satellite tracking to study naïve migrating common cuckoos. Juvenile cuckoos left breeding sites in Finland moving slowly and less consistently directed than adult cuckoos. Migration of the juveniles (N = 5) was initiated later than adults (N = 20), was directed toward the southwest-significantly different from the initial southeast direction of adults-and included strikingly long Baltic Sea crossings (N = 3). After initial migration of juvenile cuckoos toward Poland, the migration direction changed and proceeded due south, directly toward the winter grounds, as revealed by a single tag transmitting until arrival in Northwest Angola where northern adult cuckoos regularly winter. Compared to adults, the juvenile travelled straighter and faster, potentially correcting for wind drift along the route. That both migration route and timing differed from adults indicates that juvenile cuckoos are able to reach proper wintering grounds independently, guided only by their innate migration programme.